A Hedonic Analysis of Big Game Hunting Club Dues in Georgia, USA. Issue 2 (4th March 2017) - Mingie, James C.; Poudyal, Neelam C.; Bowker, J. M.; Mengak, Michael T.; Siry, Jacek P.
ABSTRACT: Hunting lease revenue can be a reliable supplemental income for forest landowners. Although studies have examined factors influencing per acre lease rates, little is known about how various characteristics are capitalized in hunting club dues. The objective of this study was to conduct a hedonic analysis of big game hunting club dues in Georgia, USA using a variety of club-, site-, and location-specific characteristics. To accomplish this objective, multivariate regression analysis was applied to explain variation in hunters' self-reported big game hunting club dues in 2012. Implicit price was then calculated for each significant covariate. Club size, presence of food plots, and game quality had positive effects on club dues, whereas membership number had a negative effect. These results should be useful for landowners and club lease managers interested in enhancing the marketability of their hunting sites and understanding the effect of management actions.